2019
DOI: 10.2174/1872208313666190404101336
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomes of Supercritical Carbon Dioxide Extract of Small Cardamom Seeds Redresses Type 2 Diabetes and Hypercholesterolemia

Abstract: Background & Objectives: In our previous investigation, oral administration of 1,8- cineole-rich supercritical carbon dioxide extract of small cardamom seeds in Wistar albino rats resulted in achieving normal fasting blood glucose (FBG) and serum cholesterol levels. The objective of this study was to further protect the aforesaid extract and to enhance its in vivo therapeutic efficacies in redressing type 2 diabetes and hypercholesterolemia, by encapsulating it as nanoliposomes. Patents related to nanolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Diabetes was induced in each rat by injecting STZ intraperitoneally at a standard dose of 60 mg/kg of the b.w. on day 1 in the morning at 09.00 hours, in accordance with the method reported by Paul et al (21) . The FBG levels were determined in STZ-injected rats after 72 h of injection.…”
Section: Administration Of Supercritical Carbon Dioxide Extracts To Hsupporting
confidence: 76%
See 2 more Smart Citations
“…Diabetes was induced in each rat by injecting STZ intraperitoneally at a standard dose of 60 mg/kg of the b.w. on day 1 in the morning at 09.00 hours, in accordance with the method reported by Paul et al (21) . The FBG levels were determined in STZ-injected rats after 72 h of injection.…”
Section: Administration Of Supercritical Carbon Dioxide Extracts To Hsupporting
confidence: 76%
“…The blood samples of all rats were estimated for FBG levels and total cholesterol, TAG, HDL and LDL were estimated in the serum samples by semi-autoanalyser (Merck), according to standard protocols (24)(25)(26)(27) . Plasma insulin levels were evaluated using ELISA kit with assay sensitivity of 0•05 mIU/l (21) .…”
Section: Administration Of Supercritical Carbon Dioxide Extracts To Hmentioning
confidence: 99%
See 1 more Smart Citation
“…CIN is widely used in the pharmaceutical industry [24] and is also used as a condiment in food and cosmetics [25]. The oral administration of CIN (550 mg/kg bodyweight) in Wistar albino rats could restore their normal fasting blood glucose and blood lipid levels [26]. The protective effect of CIN (1.1 µg/mL) on vascular endothelial injury induced by hyperglycemia has also been reported [27].…”
Section: Discussionmentioning
confidence: 96%
“…The authors suggested that cardamom essential oil-loaded nanoliposomes have potential as natural food preservative and antioxidant for a wide range of application in the food, cosmetic, nutrition, and pharmaceutical industries. Paul et al (97) formulated biotherapeutic PEGylated nanoliposomes using soya phosphatidylcholine and Tween 80 by probe-sonication to protect and enhance the therapeutic potential of green cardamom essential oil to attenuate type 2 diabetes and hypercholesterolemia. The in vitro investigations of the resultant nanoliposomes showed an entrapment efficiency of 84% and significant antioxidant activity (DPPH scavenging potency was 59%) due to antioxidant substances present in cardamom phytochemical.…”
Section: Nanoliposomesmentioning
confidence: 99%